Comparative and Inferential Study of the Development of Ethical Values in Law Students - Gonzalez, Elvira Ivone (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2016)
Quasi-experimental research design, field, cross comparing ten groups of university students in the law school from ten municipalities of Mexico State with descriptive and inference statistical analysis. Population 4.896 students of law faculties. Sample of 3.578. Material: Values and anti-values VALANTI Questionnaire and Values Test of Allport. Results: It was observed significant difference in values between students studying in different municipalities in: Economic Value, Political Value and Value Nonviolence. It should different semester’s university: Theoretical Value, Political Value and No violence Value. Noting that, in classroom behaviors modeled for professional work based on ethical and moral values.